The use of SDS-polyacrylamide gel electrophoresis in epidemiological studies of Corynebacterium diphtheriae. - Hallas, G. (Cambridge University Press, 1988)
Polyacrylamide gel electrophoresis of cell proteins was investigated as a possible typing method for Corynebacterium diphtheriae. A method was developed using stock strains which were representatives of the five gravis serotypes described by Robinson & Peeney (1936). This technique was then applied to recent isolates sent to our laboratory for identification.